New record on Asiatic Golden Cat Catopuma temminckii Vigors & Horsfield, 1827 (Mammalia: Carnivora: Felidae): photographic evidence of its westernmost distribution in Gaurishankar Conservation Area, Nepal - Narayan Prasad Koju; Bijay Bashyal; Bishnu Prasad Pandey; Shankar Thami; Man Kumar Dhamala; Satya Narayan Shah (Journal of Threatened Taxa, 2020)
The Asiatic Golden Cat Catopuma temminckii is poorly known in Nepal and was previously recorded only twice in the eastern part of the country.  We conducted a camera trap survey in the Lapchi Valley (32km2) of Gaurishankar Conservation Area (GCA), a protected area in north-central Nepal, from October 2018 to April 2019. Eleven cameras were deployed to record mammalian diversity in a 2×2 km2 grid across Lapchi block of GCA.  During the study period, four photos and three videos (each of 10 seconds length) of Asiatic Golden Cats were recorded at an elevation of 2,540m at a single camera trap station.  This is the first photographic record of Asiatic Golden Cat in this region of Nepal extending the distribution of the species further west in the Himalaya.  A more detailed study on its distribution, population size and behaviour is warranted in the near future to implement appropriate conservation measures.